2023
DOI: 10.1029/2022ja030548
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence Rates of Electromagnetic Ion Cyclotron (EMIC) Waves With Rising Tones in the Van Allen Probes Data Set

Abstract: In Fourier time‐frequency power spectrograms of satellite magnetic field data, electromagnetic ion cyclotron (EMIC) waves may feature discrete, rising tone structures that rapidly increase in frequency. Using data from the Van Allen Probes Electric and Magnetic Field Instrument Suite and Integrated Science (EMFISIS) fluxgate magnetometer, we conducted a statistical study of EMIC waves from September 2012 through June 2016. We compared the occurrence rates and spatial distributions for all EMIC waves with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 112 publications
1
11
0
Order By: Relevance
“…No matter how large the amplitude is, EMIC waves have higher occurrence rates in the northern hemisphere than that in the southern hemisphere, consistent with the results shown in Sigsbee et al. (2023) which investigates EMIC waves with rising tones. This hemispheric asymmetry feature may be related to the stronger geomagnetic activity when Van Allen Probe B was located in the northern hemisphere, as shown in Figure S2 of Supporting Information .…”
Section: Statistical Resultssupporting
confidence: 89%
“…No matter how large the amplitude is, EMIC waves have higher occurrence rates in the northern hemisphere than that in the southern hemisphere, consistent with the results shown in Sigsbee et al. (2023) which investigates EMIC waves with rising tones. This hemispheric asymmetry feature may be related to the stronger geomagnetic activity when Van Allen Probe B was located in the northern hemisphere, as shown in Figure S2 of Supporting Information .…”
Section: Statistical Resultssupporting
confidence: 89%
“…The results in Figure 5 show decrease of PSD at lower pitch angles while preserving the populations at higher pitch angles, thus narrowing the pitch angle spectra, as observed during the event and shown in Figure 5. O+ band EMIC waves are less common than He+ band EMIC waves as found by studies of EMIC observations from the Van Allen Probes era (H. Chen et al, 2019;Sigsbee et al, 2023;Yu et al, 2015); however, when O+ EMIC waves are observed, they are most prevalent in the range 3 < L < 4, which is the region where this loss is observed, and are as common as H+ EMIC waves in this region (H. Chen et al, 2019;Saikin et al, 2015). The dwell time of the spacecraft decreases with L value (as shown by H. Chen et al, 2019;Sigsbee et al, 2023;Yu et al, 2015) decreasing the likelihood of observing EMIC wave structures in this region.…”
Section: Discussionmentioning
confidence: 97%
“…Sigsbee et al. (2023) report EMIC waves are observed ∼2.4% of the time during the Van Allen Probes era, considering data from both probes. Studies by Yu et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations